Dynamical Behavior Effect of Environmental Toxinon the Prey-Predator Model - Maghool , Firas Hussean; Helal, May Mohammed (Iraqi Journal of Science, 2026)
In this research, we investigated the impact of toxins in a predator -prey paradigm where several externally harmful chemicals directly infect the prey. During feeding, the predator indirectly inherits the detrimental health. To investigate the impact of toxin-producing prey on the predator population, a mathematical model is made public. It is believed that the poison emitted by the prey population has a deleterious effect on the quantity of predators. In this paper the stability and Bifurcation, be modeled. As demonstrated by the numerical aspect addressed, the numerical solution showed that changing the parameters has an effect on the model.  The results are explained by numerical simulations. The system is shown to have an extensive array of behaviours, including chaos. The effect of toxin is to show the stability of the system, or it causes the predator to go extinct. Increasing toxins have the potential to deplete symbiosis and wipe out entire populations.